2022
DOI: 10.1155/2022/2520348
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Suppresses Macrophage M1 Polarization and ROS-Mediated Pyroptosis via Activating ApoE/LDLR Pathway in Influenza A-Induced Acute Lung Injury

Abstract: Influenza virus infection is one of the strongest pathogenic factors for the development of acute lung injury (ALI)/ acute respiratory distress syndrome (ARDS). However, the underlying cellular and molecular mechanisms have not been clarified. In this study, we aim to investigate whether melatonin modulates macrophage polarization, oxidative stress, and pyroptosis via activating Apolipoprotein E/low-density lipoprotein receptor (ApoE/LDLR) pathway in influenza A-induced ALI. Here, wild-type (WT) and ApoE-/- mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
2
7
0
Order By: Relevance
“…In COPD, pathogens infection may further evoke abnormal polarization of AMs, exacerbate lung damages of COPD patients [ 15 , 40 ]. In our previous study, acute IAV infection was found only up-regulated the M1 polarization of pulmonary macrophages [ 18 ]. We speculate that, while macrophages are in resting status, acute IAV infection dominantly polarizes them into pro-inflammatory M1 phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In COPD, pathogens infection may further evoke abnormal polarization of AMs, exacerbate lung damages of COPD patients [ 15 , 40 ]. In our previous study, acute IAV infection was found only up-regulated the M1 polarization of pulmonary macrophages [ 18 ]. We speculate that, while macrophages are in resting status, acute IAV infection dominantly polarizes them into pro-inflammatory M1 phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The IAV samples were amplified in Madin-Darby canine kidney (MDCK) cells and specific pathogen-free embryonated chicken eggs. Virus titers were assayed via the standard plaque assay on MDCK cells according to previous description [ 18 , 29 ]. MDCK cells were infected with diluted virus samples 1–2 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…more serious, it is called acute respiratory distress syndrome (ARDS) (1). Respiratory virus infection, gastric acid inhalation, sepsis and other pathogenic factors can lead to ALI, including influenza A virus, avian influenza virus, coronavirus and novel coronavirus, which caused the global pandemic (2). Viral ALI (VALI) is usually caused by diffuse capillary endothelial and alveolar epithelial injury after severe injury.…”
Section: Introductionmentioning
confidence: 99%